Impact of driving duration on hand muscle strength in people who commute for work - Sannasi, Latha (International Journal Of Community Medicine And Public Health, 2019)
Background: Urbanization has brought a lot of health issues in the citizens. Commuting for work has become more common. People around the world use different means of commute like public transport or driving a car to work. The increase in time of commute may be associated with many health hazards. In this study we try to study the impact of driving duration on hand muscle power. Methods: A prospective cross sectional study was conducted in a tertiary care hospital. About 32 persons who drive car for their work participated in this study after giving their consent. Subjects grouped in to two categories long commuters, who drive for greater or equal to one hour and short commuters less than one hour. Muscle power tested on two occasions immediately after driving and four hour after driving with a help of hand grip dynamometer. Demographic details were collected. The two groups compared for muscle power and body mass index (BMI). Results: The long commuters had less muscle power in comparison with short commuters and it was significant. The average BMI of long commuters was in obesity range were as the average BMI of short commuter is less and it was statistically significant. Conclusions: Driving for greater than one hour is associated with obesity and reduced muscle power immediately after driving.